Exploration of Waste Plastic Bottles Use in Construction - Donald Kwabena Dadzie; Abdul K Kaliluthin; D. Raj Kumar (Salehan Institute of Higher Education, 2020)
The vision of this study is geared towards the exploitation of waste plastic bottle use in construction. This review paper is centers on the recycling of waste plastic bottles as a construction material as an effort to help solve the housing deficit in most developing countries including Ghana and to save the depletion of natural resources construction materials. In Ghana, plastic wastes are discarded randomly after usage, hence scatter around in cities, choking drains, and end up threatening our ecosystem. These predominant effects from the plastic wastes have necessitated the need for countries precisely developing countries including Ghana to seek more sustainable methods to reduce the drastic amount of plastic wastes in the environment. In view of the above, this paper focused on the recycling of waste plastic bottles as a construction material as an effort to solve the housing deficit in most developing countries including Ghana and to save the depletion of natural resources construction materials (stones and sand) are very much critical. In the reviews, an effort has been made to utilize the waster plastic bottles in construction by filling the bottles with soil, sand, solid waste materials as brick or block bounded with mortar as a masonry wall or the filled bottles are used as a substitute for the production of the masonry unit production. In summary, it was concluded based on varying test result that: (1) Plastic waste bottles are cheaper to acquire than most conventional construction materials and as such concrete or brick containing any amount of plastic bottle is noted to reduce the total quantities of conventional materials required, thereby reducing the cost as well. (2) The use of plastic waste bottles in construction contributes to environmental friendliness and energy savings since buildings with walls constructed of plastic bottles maintains room temperatures and contribute to energy saving and the cost of providing an artificial thermal control system. Doi: 10.28991/cej-2020-03091616 Full Text: PDF